2017
DOI: 10.1021/acs.cgd.7b00471
|View full text |Cite
|
Sign up to set email alerts
|

CH3-Tagged Bis(pyrazolato)-Based Coordination Polymers and Metal–Organic Frameworks: An Experimental and Theoretical Insight

Abstract: The novel coordination polymers M(Me 2 BPZ) (M = Co, Zn; H 2 Me 2 BPZ = 3,3′-dimethyl-1H,1′H-4,4′-bipyrazole), M(H 2 Me 2 BPZ)(CH 3 COO) 2 -(H 2 O) 2 (M = Co, Ni), and Cu(H 2 Me 2 BPZ)(Cl) 2 were isolated along conventional or solvothermal routes. Their crystal structure was unveiled by powder X-ray diffraction (PXRD), while their thermal stability was assessed by coupling thermogravimetric analysis to variable-temperature PXRD. The textural properties of the M(Me 2 BPZ) (M = Co, Zn) compounds, featuring three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…The isosteric heat of adsorption (Figure ) reflects the interaction strength between CO 2 and the walls of the channels in Zn‐BPZNO 2 : the value of 20.5 kJ mol −1 at zero coverage (calculated as the arithmetic mean value after the application of the Clausius–Clapeyron equation on pairs of datasets) falls in the ideal range for CO 2 ‐capture materials and denotes that only physisorption is at work. The Q st value of Zn‐BPZNO 2 is comparable to that of Zn(BPZ) (23.7 kJ mol −1 ); the amount of CO 2 adsorbed though is higher at the same temperature, because of its higher surface area (916 vs. 778 m 2 g −1 , respectively).…”
Section: Resultsmentioning
confidence: 80%
See 4 more Smart Citations
“…The isosteric heat of adsorption (Figure ) reflects the interaction strength between CO 2 and the walls of the channels in Zn‐BPZNO 2 : the value of 20.5 kJ mol −1 at zero coverage (calculated as the arithmetic mean value after the application of the Clausius–Clapeyron equation on pairs of datasets) falls in the ideal range for CO 2 ‐capture materials and denotes that only physisorption is at work. The Q st value of Zn‐BPZNO 2 is comparable to that of Zn(BPZ) (23.7 kJ mol −1 ); the amount of CO 2 adsorbed though is higher at the same temperature, because of its higher surface area (916 vs. 778 m 2 g −1 , respectively).…”
Section: Resultsmentioning
confidence: 80%
“…The porous nature of the MOFs was investigated through N 2 adsorption at 77 K; Ta ble 1c ollectst he main results.A ss hown in Figure 5, all the compoundss how at ype IV isotherm, typical of am icro-mesoporous material. Zn-BPZNO 2 has the highest BET area with av alue of 916 m 2 g À1 ,w hereas the cobalt(II) and copper(II) MOFs show BET areas of 645 and 408 m 2 g À1 ,r espectively.O verall, the recordedB ET areas fall in the same range as those of the parent MOFs containing the simple BPZ 2À spacer [31,33] and are highert han those found fort he isotypical M-Me 4 BPZ compounds (396, 318, and 376 m 2 g À1 for M = Zn, Co, and Cu, respectively), [32] which is in line with the increased steric hindranceo ft he four methyl groups if compared to a single nitro substituent. The t-plot analysis revealed that the main contribution to the total surface area comesf rom the micropores (77, 75, and 51 %o ft he total specific surface area (SSA) for Zn-BPZNO 2 ,C o-BPZNO 2 ,a nd Cu-BPZNO 2 ,r espectively).…”
Section: N 2 Adsorptionmentioning
confidence: 70%
See 3 more Smart Citations